2014
DOI: 10.3389/conf.fmars.2014.02.00003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different drying conditions on the rehydration ratio and water holding capacity properties in three different species of algae Ulva lactuca, Codium vermilara and Codium tomentosum

Abstract: Over the last years, algae have been increasingly used in Human food due their rich chemical and nutritional composition, particularly the high supply of essential nutrients to the human body such as protein and dietary fiber. Dietary fiber can be divided into two different types: soluble and insoluble. The characteristics of soluble dietary fiber are related to some physical and chemical properties such as rehydration ratio and water holding capacity and are important in assigning the functional and organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…To our knowledge, the effect of oven-drying on valuable compounds of Ulva , Gracilaria and Fucus genre has been scarcely studied. Robic et al [20] evaluated the impact of oven-drying at 50 and 70 °C, on the yield of recovery and physicochemical features of ulvans, obtained from wild Ulva rotundata of France origin, while Rodrigues et al [21] focused the rehydration ratio and water holding ability of Ulva lactuca (unspecific origin) oven-dried at 30 and 40 °C. Lastly, recently, Uribe et al [22] studied the impact of different drying methods, including oven-drying at 70 °C, on the surface color and phytochemical content and amino acid and fatty acid profiles of wild Ulva spp.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the effect of oven-drying on valuable compounds of Ulva , Gracilaria and Fucus genre has been scarcely studied. Robic et al [20] evaluated the impact of oven-drying at 50 and 70 °C, on the yield of recovery and physicochemical features of ulvans, obtained from wild Ulva rotundata of France origin, while Rodrigues et al [21] focused the rehydration ratio and water holding ability of Ulva lactuca (unspecific origin) oven-dried at 30 and 40 °C. Lastly, recently, Uribe et al [22] studied the impact of different drying methods, including oven-drying at 70 °C, on the surface color and phytochemical content and amino acid and fatty acid profiles of wild Ulva spp.…”
Section: Introductionmentioning
confidence: 99%
“…is widely distributed throughout the world and one of the two Chlorophyta genera allowed for consumption as vegetables and condiments in Europe [11], but still, the scientific knowledge about the impact of preservative processing in this genus is quite limited and only performed at a laboratory scale. In particular, Robic et al [12] evaluated the impact of oven-drying (50 and 70 °C) on the yield of recovery and physicochemical features of ulvans, obtained from wild Ulva rotundata , while Rodrigues et al [13] reported the influence of oven-drying (30 and 40 °C) on the rehydration ratio and water holding ability of Ulva lactuca . In turn, Uribe et al [14] evaluated the effect of distinct drying methods, namely freeze-, vacuum-, solar-, and convective drying (at 70 °C), on the surface color of wild Ulva spp.…”
Section: Introductionmentioning
confidence: 99%